2017
DOI: 10.1016/j.jsbmb.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 binds to vitamin D receptor and decreases vitamin D-induced growth suppression

Abstract: Receptor interacting protein kinase 1 (RIPK1) is an enzyme acting downstream of tumor necrosis factor alpha to control cell survival and death. RIPK1 expression has been reported to cause drug resistance in cancer cells, but so far, no published studies have investigated the role of RIPK1 in vitamin D signaling. In the present study, we investigated whether RIPK1 plays any roles in 1,25-dihydroxyvitamin D3 (1,25D3)-induced growth suppression. In our studies, RIPK1 decreased the transcriptional activity of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Venous blood Samples were taken for the es ma on of 25(OH) Vitamin D, Calcium and Phosphate. Sta s cal analysis was done using SPSS so ware version 16.…”
Section: Methodsmentioning
confidence: 99%
“…Venous blood Samples were taken for the es ma on of 25(OH) Vitamin D, Calcium and Phosphate. Sta s cal analysis was done using SPSS so ware version 16.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the observation, RIPK1 was found that formed a complex with VDR and retained VDR in cytoplasm in MEFs and ovarian cancer cells. The formed complex not only blocked transcriptional activity of VDR, but also disturbed the necrosome formation (225).…”
Section: Vitamin D and Regulated Necrosismentioning
confidence: 99%
“…This might be achieved through the shift of VDR from the nucleus into the cytosol or through the retention of VDR in the cytosol. 35 Despite the overall reduction in VDR expression in colitis, VDR expression in the cytosol actually increased and thereby influenced the formation of the RIPK1/3 complex and subsequently relieved inflammatory responses by inhibiting necroptosis. This process might be a negative loop through which intestinal epithelial cells protect themselves in the case of colitis.…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, the key components in the necroptotic pathway, such as caspase-8 and RIPK3, play multi-directional roles in the balance between the pathways of cell death and process of tissue repair. 35 Our future studies will focus on the specific role of each necroptotic protein in response to vitamin D treatment in colitis.…”
Section: F I G U R Ementioning
confidence: 99%